REMEDIASI MISKONSEPSI MENGGUNAKAN LKPD BERBASIS CROSSWORD PUZZLE MATERI TEKANAN ZAT CAIR DI SMP - Wahdini, Rahmatika; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstractthis research aimed to remediated of studentâ€™s misconceptions used LKPD based crossword puzzles on liquid pressure in Junior High School 6 Pontianak. This research used experiment method with pre-experimental design form used one group pretest-posttest design. This research used intact group technique which the outcome is class of VIII C with 32 students. The instrument of this research is a diagnostic test consist of 9 multiple choice questions. Based on the data analysis, the mean percentage of student's misconception decreasing is 44,26%. Mc Nemar statistic test result with dk = 1 and Î± = 5%showed > , this result showed that there is a significant change of the students' conception. The effect size of LKPD based crossword puzzle in the remediation of misconception is 1,49 (high category). It is expected to be used as an alternative teaching physics remediation to student's misconceptions.Â Keywords: Remediation, Misconceptions, LKPD, Crossword Puzzles, Liquid PressureÂ